Grain quality and yield potential of hybrids from quality and non-quality protein maize inbred lines. (September 2022) - Amegbor, I.K.; van Biljon, A.; Shargie, N.; Tarekegne, A.; Labuschagne, M.T.
Abstract: Identification of maize hybrids with enhanced quality trait(s) is important for addressing malnutrition among the increasing human population. The objective of this study was to assess quality trait performance of quality protein maize (QPM) and non-QPM lines crossed with QPM and non-QPM testers. A total of 130 hybrid progenies (48 QPM x QPM, 64 QPM x non-QPM and 18 non-QPM x non-QPM) were generated from QPM and non-QPM lines and testers. Two QPM and three non-QPM checks were included and these 135 hybrids were evaluated in field experiments across six locations. The QPM x QPM hybrid group had a protein quality index (QI) and tryptophan content value of 0.99 and 0.078 respectively, compared to the 0.55 and 0.048, and 0.5 and 0.045, of the QPM x non-QPM and non-QPM x non-QPM group, respectively. This indicated a loss of the tryptophan and QI advantage caused by the opaque2 gene in QPM in the QPM x non-QPM crosses. Therefore, to retain nutritional value, QPM should not be allowed to cross with non-QPM maize. The average protein content of the QPM x QPM group (7.9%) was significantly lower than that of the QPM x non-QPM (8.74%) and non-QPM x non-QPM groups (9.03%). Some QPM hybrids did have excellent yield and nutritional value and can be promoted for commercial release. Graphical abstract: Image 1 Highlights: QPM has double the amount of essential amino acids lysine and tryptophan of non-QPM. QPM and non-QPM lines and testers were crossed and nutritional value determined. QPM x non-QPM hybrids had lower tryptophan and protein QI than QPM x QPM. QPM had significantly lower protein content than non-QPM. QPM x non-QPM hybrids lost the advantages of the opaque2 gene.